2019
DOI: 10.1136/bmjspcare-2019-002016
|View full text |Cite
|
Sign up to set email alerts
|

Patients' spirituality perspectives at the end of life: a qualitative evidence synthesis

Abstract: BackgroundUnderstanding patient perceptions of their spiritual needs when approaching the end of life is essential to support the delivery of patient-centred care.AimTo conduct a qualitative evidence synthesis on spirituality and spiritual care needs at the end of life in all healthcare settings from the patients’ perspective.DesignStudies were included where they were primary qualitative studies exploring spirituality in patients with a life expectancy of 12 months or less in any setting. Two reviewers indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 71 publications
0
27
0
1
Order By: Relevance
“…34 Previous reviews only incorporated qualitative studies. [30][31][32] (Cagle, Bunting and Kelemen, 2017).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…34 Previous reviews only incorporated qualitative studies. [30][31][32] (Cagle, Bunting and Kelemen, 2017).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Previous reviews have identified recurrent themes that encompass patients' needs concerning the spiritual dimension. [30][31][32] These themes concern, amongst others, a "need for meaning," "need for relationships," "need for control" and "need for independence." Throughout these reviews and some primary studies, these themes frequently recur, although sometimes phrased differently.…”
Section: Recurrent Themes Of Patients' Needsmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes factors related to physical environment (e.g., infrastructure related both in terms of equipment and to create a private, personalized, and comfortable space such as a single room with a window and less visible technology), 49,53,64,[103][104][105][106][107][108][109] organizational environment (e.g., healthcare setting and design characteristics that promote familiarity and openness), 69,76,110 and social environment (e.g., environmental facilitation of social interactions that allow closeness to others such as with regular caregiver visits, stimulating activities that are 'positive distractions', and activities of daily living including the practice of spirituality). 108,109,111,112 These resource elements account for the influence of environment on facilities functioning, including safety. 103,108,113 Sub-domain 5, knowledge and evidence for policy and practice, is premised on the collection and utilization of accurate patient-centered data, 114 alongside other health system performance indicators, and development of applicable metrics that capture local needs.…”
Section: Domain 2: Resource Generationmentioning
confidence: 99%
“…93 Integrating access to clergy or chaplain was reported to provide comfort and healing for spirit maintenance. 111,191 Sub-domain 5, access to social care, is for professional management of social distress by social care specialists or social workers that facilitate support and access to resources. 30,170,192 It is interconnected with psychological suffering and contributes to addressing psychosocial needs.…”
Section: Domain 4: Service Provisionmentioning
confidence: 99%